A closer relationship between working and learning? Employers and distance learners talk about developing work skills - Pegg, Ann (Arbetsmarknad & Arbetsliv, 2018)
Across Europe universities are expected to work more closely with employers to ensure that learners develop employability skills for the workplace. Policy discourse suggests that a closer relationship between universities and employers can act as a mechanism to develop employability skills more effectively. This article draws on a small qualitative case study which investigated the “Graduate@ Work” initiative undertaken by the Open University. These distance learners, sponsored by their SME employers, were already working and the research investigated employer and student understandings of the connections between employability skills, working and learning and whether facilitating a closer relationship between the university and employers would enable more effective learning in relation to the workplace.